Efektivitas Media Audio Visual terhadap Keterampilan Istima’ di MI Muhammadiyah Gembuk 1 - Indriani Permata Kusumadewi; Itsnaini Muslimati Alwi; Sanjaka Yekti (Naskhi: Jurnal Kajian Pendidikan dan Bahasa Arab, 2022)
This study examines the effectiveness of audio-visual media on the Arabic language skills of fifth grade students of MI Muhammadiyah Gembuk 1. This study used quasi-experimental with a quantitative approach using three requirements, namely controlling, manipulating, and observing activities. The research activity was carried out in class V MI Muhammadiyah Gembuk 1, with a sample of 10 students. The study was conducted from February to March 2022. The results showed that: (1) there was no significant difference between students who took lessons using audio media and students who took listening lessons, with the same score as Asymp.Sig.(- 2tailed) on the use of audio-visual media is 0.000 <0.05 and Asymp.Sig. (2-tailed) 0.000 < 0.05 in listening learning. (2) there is a significant difference between students who take part in learning using audio-visual media and students who take part in listening lessons, with the acquisition of the N-gain value on the use of audio-visual media is 0.310, while the value of 0.242 in listening learning. (3) Audio-visual media is effectively used in learning Arabic, especially in special skills.